SMU launches Analytics and Cloud Technology Work-Study Programme with Google and KPMG - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
The Singapore Management University’s (SMU) School of Computing and Information Systems (SCIS) has launched a new SMU-KPMG Analytics and Cloud Technology Work Study Programme in partnership with Google. Students enrolled in this programme will acquire a Google Career Certificate via a scholarship before embarking on a six-month extended internship with KPMG.